Pendidikan Kewarganegaraan di Era Digital: Tinjauan Literatur tentang Tantangan dan Inovasi Pembelajaran Abad Ke-21 - Via Nur Oktavia; Arik Darojat (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
Digital transformation has brought significant changes to the world of education, including in Pancasila and Citizenship Education (PPKn) learning. Developments in information technology not only influence how teachers deliver material but also shape patterns of interaction, participation, and student civic literacy. This article aims to systematically examine the various challenges and innovations in PPKn learning in the digital era through a literature study approach. The method used is a systematic literature review of national and international journal articles published in the last ten years, obtained through Google Scholar, SINTA, and Scopus databases. Data were analyzed using thematic analysis techniques to identify key findings related to technology utilization, implementation constraints, and its impact on students' civic competence. The results of the study indicate that digital-based PPKn learning has the potential to increase participation, understanding of civic concepts, and strengthening students' democratic character. However, major challenges still include limited teacher digital competence, access to technological infrastructure, and curriculum readiness to accommodate learning innovations. This article provides practical implications for teachers, curriculum developers, and policymakers in designing PPKn learning strategies that are adaptive, inclusive, and relevant to the demands of the 21st century.